Aquaporin OsPIP2;2 links the H2O2 signal and a membrane-anchored transcription factor to promote plant defense. Issue 4 (27th December 2021) - Zhang, Mou; Shi, Haotian; Li, Ningning; Wei, Nana; Tian, Yan; Peng, Jinfeng; Chen, Xiaochen; Zhang, Liyuan; Zhang, Meixiang; Dong, Hansong
Abstract: To overcome pathogen infection, plants deploy a highly efficient innate immune system, which often uses hydrogen peroxide (H2 O2 ), a versatile reactive oxygen species, to activate downstream defense responses. H2 O2 is a potential substrate of aquaporins (AQPs), the membrane channels that facilitate the transport of small compounds across plasma membranes or organelle membranes. To date, however, the functional relationship between AQPs and H2 O2 in plant immunity is largely undissected. Here, we report that the rice ( Oryza sativa ) AQP OsPIP2;2 transports pathogen-induced apoplastic H2 O2 into the cytoplasm to intensify rice resistance against various pathogens. OsPIP2;2-transported H2 O2 is required for microbial molecular pattern flg22 to activate the MAPK cascade and to induce the downstream defense responses. In response to flg22, OsPIP2;2 is phosphorylated at the serine residue S125, and therefore gains the ability to transport H2 O2 . Phosphorylated OsPIP2;2 also triggers the translocation of OsmaMYB, a membrane-anchored MYB transcription factor, into the plant cell nucleus to impart flg22-induced defense responses against pathogen infection. On the contrary, if OsPIP2;2 is not phosphorylated, OsmaMYB remains associated with the plasma membrane, and plant defense responses are no longer induced. These results suggest that OsPIP2;2 positively regulates plant innate immunity by mediating H2 O2 transport into the plant cell and mediating the translocation of OsmaMYB from plasma membrane to nucleus. Abstract : A rice AQPs acts as a positive immune regulator by transporting H2 O2 and modulating a membrane-anchored transcription factor.